Analisis Faktor-Faktor Fundamental yang Mempengaruhi Harga Saham (Studi Kasus Pada Perusahaan Manufaktur yang Terdaftar LQ45 di Bursa Efek Indonesia Periode 2012-2017) - Fatchur Rohman; Talchis Afkar (Accounting Study Program, Faculty of Economics and Business, 2018)
In general, it can be said that information about the company can assist the assessment in making decisions. One of the main information needed is accounting information. The purpose of this study was to determine the effect of fundamental factors on stock prices listed on the Indonesia Stock Exchange. This research data was collected by survey method on LQ45 manufacturing companies listed on the Indonesia Stock Exchange. The types and sources of data used in this study are secondary data consisting of reports on Net Profit Margin, Return On Assets, Return On Equity, Return On Investment, Earning Per Share, Price Earning Ratio, and Price to Book Value. Secondary data sources come from Indonesian www.idx.co.id. The research data were then analyzed using the SPSS version 20.0 program significant effect of Return On Assets and Earnings Per Share on stock prices. There is no significant effect of Net Profit Margin, Return On Assets, Return On Equity, Return On Investment, Price Earning Ratio and Price to Book Value on Stock Prices. This is because the observation period for 6 years affected R square by 77.%. So the effect is quite large from the 7 ratio measuring tools used. While 23% is explained by other factors such as political and economic conditions.